2018
DOI: 10.1111/jsr.12744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sleep deprivation on emotional working memory

Abstract: The emotional dysregulation and impaired working memory found after sleep loss can have severe implications for our daily functioning. Considering the intertwined relationship between emotion and cognition in stimuli processing, there could be further implications of sleep deprivation in high-complex emotional situations.Although studied separately, this interaction between emotion and cognitive processes has been neglected in sleep research. The aim of the present study was to investigate the effect of 1 nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…These all can prove the existence of the effect of SD, with or without a sham rTMS condition in the study. In addition, specifically for emotional working memory, one night of SD may just impair the accuracy but not reaction time [41]. This similar performance was observed after rTMS in our study and just showed significant change in the response accuracy of the number test but not reaction time.…”
Section: Working Memory and Alff Changes After Sdsupporting
confidence: 87%
See 1 more Smart Citation
“…These all can prove the existence of the effect of SD, with or without a sham rTMS condition in the study. In addition, specifically for emotional working memory, one night of SD may just impair the accuracy but not reaction time [41]. This similar performance was observed after rTMS in our study and just showed significant change in the response accuracy of the number test but not reaction time.…”
Section: Working Memory and Alff Changes After Sdsupporting
confidence: 87%
“…Growing evidence has demonstrated the critical impairments of SD on various cognitive abilities, especially on working memory both in younger and older healthy adults, after total SD or partial SD [14,15,[39][40][41][42][43]. Behavioral results of almost all these past studies found that subjects showed a significantly lower response accuracy rate, longer reaction time, and higher lapse rate on the working memory test after SD 4…”
Section: Working Memory and Alff Changes After Sdmentioning
confidence: 99%
“…The task and study protocol were the same as reported recently for younger adults (Gerhardsson et al, 2019). All participants performed a practice run of the emotional working memory task in relation to the screening interview 1 week before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in young adults, lack of sleep causes alterations in emotional processing (Tempesta et al, 2018), primarily by increased reactivity to emotional stimuli and an impaired ability to regulate emotional reactivity (Yoo et al, 2007; Gujar et al, 2011). We recently reported that sleep deprived younger adults (18–30 years), but not the controls (with full sleep), responded faster to positive and slower to negative relative to neutral pictures on an emotional working memory task, which could be interpreted as a positivity effect (Gerhardsson et al, 2019). We also found that sleep deprivation overall impaired accuracy and omission rate, but not reaction times.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of evidence that one's emotional state can moderate performance in certain cognitive tasks, sometimes referred to as the difference between hot cognition (when cognition can be influenced by emotional state) and cold cognition (cognitive performance that is not influenced by emotion) (Smilek & Frischen, 2013). Examples of sleep loss leading to changes in hot cognition include one study that found sleep deprivation caused valence-specific performance changes in an emotional working-memory task (Gerhardsson et al, 2019). Another example comes from the effects of sleep loss on emotionally dependent decision making tasks (Pace-Schott, Nave, Morgan, & Spencer, 2012).…”
Section: The Effect Of Sleep Loss On Emotional Functioningmentioning
confidence: 99%